The antidepressant effects of kaji-ichigoside F1 via activating PPAR-γ/CX3CR1/Nrf2 signaling and suppressing NF-κB/NLRP3 signaling pathways - Huang, Maoyang; Chen, Faju; Zhou, Lang; Zhang, Qing; Wang, Li; Li, Liangqun; Yang, Lishou; Gao, Ming; Li, Lilang; Wang, Yu; Yang, Juan; Yao, Guanping; et al. (Frontiers in Pharmacology, 2025)
IntroductionDepression is a mental illness closely associated with neurological damage and is characterised by high rates of suicide and mood changes. As a traditional medicinal plant, Rosa roxburghii Tratt has been widely used since ancient times in the Miao and Dong regions of Southwest China for the relief of sleep disorders, indigestion, anti-inflammation, neurasthenia and neuroprotection. The total triterpenes of R. roxburghii were previously found to have certain neuroprotective effects, and whether Kaji-ichigoside F1 (KF1), as its main ingredient, plays a relevant pharmacological role needs to be further investigated.MethodsEstablishment of mouse depression model and BV2 microglia inflammation model using intraperitoneal injection of LPS in mice and LPS stimulated-BV2 microglia, respectively. The antidepressant effects of KF1 were evaluated by forced swim test (FST), sucrose preference test (SPT), tail suspension test (TST) and open field test (OFT). The number of Nissl bodies and apoptotic positive cells in the CA1 region of the hippocampus was observed by Nissl and TUNEL staining. Then, the levels of TNFα, PPAR-γ, TGF-β, and IL-6 cytokines were tested by ELISA kits. Finally, the molecular mechanisms were investigated by Western blotting (WB) and immunofluorescence in vivo and in vitro.ResultsKF1 dramatically ameliorated LPS-induced depressive like behaviors, neuronal damage, apoptosis, and suppressed the levels of pro-inflammatory cytokines in the serum and hippocampus of mice. Our vitro experiment also showed KF1 significantly reduced cell viability and attenuated apoptosis in LPS-induced BV2 microglia, decreased the mean fluorescence intensity of Caspase-1, TNFα, NF-κB, IL-1β, NLRP3, and Keap1. However, the mean fluorescence intensity of GCLC, GCLM, GST, SOD1, HO-1, and Nrf2 were significantly increased. Finally, Western blot analysis showed that KF1 suppressing the expression of NF-κB/NLRP3 signaling pathway and activating PPARγ/CX3CR1/Nrf2 signaling pathway both in vivo and in vitro.ConclusionIn conclusion, these results suggest that KF1 is an effective alleviator of LPS-induced depression-like effects in vivo and in vitro. These effects were associated with activating PPARγ/CX3CR1/Nrf2 signaling, and suppressing NF-κB/NLRP3 signaling pathways.